The Problems Faced in Study Periods and in Leisure-Time Activities at Regional Boarding Primary Education Schools: A Case Study of Elazig - Kazu, Ibrahim Yasar; Askin, Zehra (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2011)
The purpose of this study is to present the problems faced at study periods and leisure-time activities at the Regional Boarding Primary Education Schools and propose solutions to these problems. The population of the study is the Regional Boarding Primary Education Schools (YIBOs) in Elazig. As the data gathering instrument, a half-structured questionnaire has been administered to the teachers. Data gathered from meetings have been analyzed and interpreted using context analysis. The assembled finding, following the interpretation of the questionnaire items, indicates that these schools are physically inadequate, the study and hobby rooms are particularly unsatisfactory and these rooms need to be reconstructed. Problems regarding the shift system of the supervisor teachers also need to be resolved. It is apparent that the Regional Boarding Primary Education Schools are common in the country and their number varies from one district to another. The aim of this study is to aid the determination of and solutions to, the problems at Regional Boarding Primary Education Schools.
Keywords: Regional Boarding Primary Education Schools (YIBOs); study periods; leisuretime activities